Análisis de la conectividad en la Unidad Educativa “General Vernaza” de la Parroquia General Vernaza - Cajo Ramos, Jomayra Alexandra (2020)
The summary of the present case study consists of carrying out a connectivity analysis in the “General Vernaza” Educational Unit, which is located in the General Vernaza Parish belonging to the Salitre canton, to verify the shortcomings that are occurring in the connectivity of the Educational Unit. "General Vernaza" and thus propose alternative solutions that allow the optimal functioning of the established network. The “General Vernaza” Educational Unit, like many other educational institutions, has a computer network with internet access that benefits both students and teachers and administrative staff. This network is presenting connectivity problems, which is why a exhaustive analysis of the established network system. Where it could be verified that said institution does not have an adequate infrastructure, it also does not have adequate maintenance to protect the equipment from the environment they face every day, and it was observed that the equipment installed does not meet the necessary characteristics to offer a service to the number of devices that require access to the network.